Compatibility Study of Ship Dimension Ratios with Fish Traps and Hand Lines at PPN Palabuhanratu - Rizal, Daisy Rahma; Dinata, Syafril Mayu; Anjasmara, Aang Setyawan; Sarifuddin, Andri (Jurnal Perikanan Terpadu, 2025)
Fishing vessels are generally made using traditional methods that have been passed down from generation to generation. The characteristics of fishing vessels can be determined from the main dimensions of the vessel, the fishing gear used and the fishing area. This study is needed because inappropriate fishing vessel dimensions can affect the seaworthiness of the vessel and operational efficiency, especially in small-scale fisheries. This study aims to evaluate the suitability of the ratio of the main dimensions of the vessel to the types of fishing gear, namely traps and handlines at the Palabuhanratu Archipelago Fisheries Port (PPN). Data in the form of measurements of the length (L), width (B), and height (D) of the vessel were collected in the field, while comparative data were obtained from previous literature. The analysis was carried out by calculating the L/B, L/D, and B/D ratios, then compared with the main dimension ratios of static gear vessels as a reference. The results showed that the L/B ratio of trap vessels ranged from 7.5–10 with an average of 7.93, while handlines were 5–12.5 with an average of 9. The L/D ratios of trap and handlines were respectively 11.5 and 11.83. The B/D ratio of the trap and handline fishing vessels were 1.13-1.63 and 0.57-2.25, respectively. The B/D ratio indicates that there are vessels with values below standard, indicating the potential for less than optimal stability. In general, vessels in PPN Palabuhanratu are still within the standard range, although there are several handline fishing vessels that need more attention regarding their stability design. Improvements in vessel design based on appropriate dimension ratios are expected to increase operational efficiency, safety, and sustaina